Aplikasi Self Management untuk Mencatat Jadwal Kegiatan Dengan Speech to Text Menggunakan Google API Berbasis Android - Kevin Angka Wijaya; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2022)
Self Management is a person's ability to control himself against an action. But there are still many people who underestimate this, especially in terms of scheduling activities. People tend to only rely on memory and organize activities incorrectly. This makes people think a lot and tend to forget things. Thus, a scheduler app can be a perfect solution for busy people. This paper was made to create an application for scheduling using speech to text. The features of the application are calendars, to-do lists, notes, and speech to text. Speech to text using the Google Speech API. Calendar connects directly to Google Calendar using the Google Calendar API. Other features are stored in a local database in the form of SQLite. The application was tested by measuring the speed of making a schedule using a stopwatch. The result is that the schedule can be made in 10.426 seconds using speech to text. By using the Google Speech API in making the schedule, the accuracy obtained reaches 96.45%.